Applying an Implementation Science Framework for Adoption of a Comprehensive Program for High School Students With Autism Spectrum Disorder. (March 2014) - Odom, Samuel L.; Duda, Michelle A.; Kucharczyk, Suzanne; Cox, Ann W.; Stabel, Aaron
Post-school outcomes for adolescents and young adults with autism spectrum disorder (ASD) are exceedingly poor. The convergence of adolescence as a development period, the expression of ASD during adolescence, and the complicated logistic nature of high schools create a perfect storm of complexity that may pose challenges and establish barriers to providing an effective secondary education program. Given this complexity, addressing learning needs for adolescents with ASD and improving post-school outcomes requires a comprehensive approach. In this article, the authors describe a set of implementation science principles and practices that could be employed in supporting the adoption and implementation of a comprehensive program for high school students with ASD. The program developed by the Center on Secondary Education for Students With Autism Spectrum Disorder (CSESA) serves as a case example of how such principles and practices may be employed in program planning and implementation.